Flow network control via substituted flows determining the ratio of parallel flows. Issue 13 (2019) - Neifer, Alexander; Appel, Marcus; Walther, Michael; Konigorski, Ulrich
Abstract: Nowadays, flow networks are usually discussed with respect to optimal flows but not from a control theory point of view. This paper combines these two perspectives to provide a new approach to apply control theory to flow networks building on structural and hierarchical considerations. The flow network is substituted iteratively through several hierarchical layers to simplify the problem. A method to exploit available degrees of freedom by trade-off parameters is presented. These parameters can be used to distribute the flow in parallel flow lines to achieve further control objectives. For that matter the structural properties are used to iteratively define substitute flows simplifying the flow network. This concept gives the advantage to define the ratio of parallel flows during the controller design process. Once the controller is designed the flows can be adjusted online by the trade-off parameters. We demonstrate our method in two scenarios considering different disturbances.